Primary Results of the Multicenter ARISE II Study (Analysis of Revascularization in Ischemic Stroke With EmboTrap). Issue 5 (May 2018) - Zaidat, Osama O.; Bozorgchami, Hormozd; Ribó, Marc; Saver, Jeffrey L.; Mattle, Heinrich P.; Chapot, René; Narata, Ana Paula; Francois, Olivier; Jadhav, Ashutosh P.; Grossberg, Jonathan A.; Riedel, Christian H.; Tomasello, Alejandro; et al.
Abstract : Background and Purpose—: EmboTrap is a novel stent retriever designed to achieve rapid and substantial flow restoration in acute ischemic stroke secondary to large-vessel occlusions. Here, we evaluated EmboTrap's safety and efficacy compared with established stent retrievers. Methods—: ARISE II (Analysis of Revascularization in Ischemic Stroke With EmboTrap) was a single-arm, prospective, multicenter study, comparing the EmboTrap device to a composite performance goal criterion derived using a Bayesian meta-analysis from the pivotal SWIFT (Solitaire device) and TREVO 2 (Trevo device) trials. Patients at 11 US and 8 European sites were eligible for inclusion if they had large-vessel occlusions and moderate-to-severe neurological deficits within 8 hours of symptom onset. The primary efficacy end point was achievement of modified Thrombolysis in Cerebral Ischemia (mTICI) reperfusion scores of ≥2b within 3 EmboTrap passes as adjudicated by the core laboratory. The primary safety end point was a composite of symptomatic intracerebral hemorrhage and serious adverse device effects. Secondary end points included functional independence (modified Rankin Scale, 0–2) and all-cause mortality at 90 days. Results—: Between October 2015 and February 2017, 227 patients were enrolled and treated with the EmboTrap device. The primary efficacy end point (mTICI ≥2b within 3 passes) was achieved in 80.2% (95% confidence interval, 74%–85% versus 56% performance goal criterion; P value, <0.0001), and mTICI 2c/3 was 65%. After all interventions, mTICI 2c/3 was achieved in 76%, and mTICI ≥2b was 92.5%. The rate of first pass (mTICI ≥2b following a single pass) was 51.5%. The primary safety end point composite rate of symptomatic intracerebral hemorrhage or serious adverse device effects was 5.3%. Functional independence and all-cause mortality at 90 days were 67% and 9%, respectively. Conclusions—: The EmboTrap stent-retriever mechanical thrombectomy device demonstrated high rates of substantial reperfusion and functional independence in patients with acute ischemic stroke secondary to large-vessel occlusions. Clinical Trial Registration—: URL:http://www.clinicaltrials.gov . Unique identifier: NCT02488915. Abstract : Supplemental Digital Content is available in the text.